E-MAGAZINE TO IMPROVE BIOLOGICAL CRITICAL THINKING ABILITY - Siti Hajar; Rita Istiana; Indri Yani (ATRIUM PENDIDIKAN BIOLOGI, 2022)
In the industrial revolution 4.0, technology has become the basis of human life to design learning media, in improving students' critical thinking skills in the immune system learning process. This study aims to determine thelearning media e-magazine on immune system material can improve students' critical thinking skills and the process of developing e-magazines as learning media. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). This research was conducted at Madrasah Aliyah Negeri (MAN) 2 Sukabumi. This research was conducted in December 2020 - August 2021. The population and sample of this study were 30 students of Madrasah Aliyah Negeri (MAN) 2 Sukabumi class XI IPA 2. Implementation of a limited trial using aresearch design one group pretest-posttest. The results showed that e-magazine can improve students' critical thinking skills, with an increase in the percentage of 41.06% and the n-gain of 0.65 in the medium category. As for the development process, the results showed that the e-magazine product named Immune System Magazine (IS-Magz) contains material on the immune system including understanding, functions, influencing factors, defense mechanisms, and immune system disorders, and is equipped with various supporting features such as flashes. info, updates journal, true stories, learning videos, important info, discussions, and quizzes to improve the material contained in the e-magazine.